Influence of Technological Orientation on Performance of Conventional and Islamic Banking in Kenya: A Non-experimental and Causal Approaches - Osore, Saleh Anyango; Ngugi, Patrick Karanja; Ogollah, Kennedy (Modern Perspectives in Economics, Business and Management Vol. 1, 2021)
Background: Information technology has contributed to increasing the probability of success of online marketing by increasing the possibility of advertising new and current services at any time and everywhere. It has contributed to connecting the ground to some and thus increasing the user segment. Purpose: The research was done to establish the influence of technological orientation on performance of Conventional and Islamic banking in Kenya. Methodology: The study adopted a mixed methods research design based on descriptive, non- experimental and causal approaches. This study considered a census that targeted a population of all the forty three (43) commercial banks that were operational in Kenya as at 31st December 2016. The commercial banks also consist of Islamic banks which offer Shari’ah compliant products and services. This study used a questionnaire as the main instrument for primary data collection. Data preparation started start by coding and cleaning, the primary data obtained from the questionnaires were checked for omissions, legibility and consistency before being coded for analysis. Processed data was analysed by using both descriptive and inferential statistics. Stata version 15 was be used for statistical analysis and presentation tables of the results processed in Microsoft excel. Descriptive analysis was done for the observed indicators and presented as frequency, percentages, mean and standard deviation to reveal the distribution trends. The data collected was in the form of observed indicators of larger constructs thus multivariate dimension reduction techniques (factor analysis) was be used to form composite latent constructs. The latent constructs generated after dimension reduction were used for statistical modelling. Results: The findings indicated that Technical Orientation was considered as an independent variable and dimension of Strategic Orientation. It was considered to have 3 dimensions Services, Products and Research and Development. The latent construct technical orientation yielded from factor analysis dimension reduction of the indicators was then used as an independent variable in a regression model fitted against firm performance which showed that it was not a significant level-2 random covariate but had a significant coefficient estimate at the respondent level (level-1). The coefficient of technical orientation on performance at level one was found to be 0.828 which implied that increasing the levels of TO by a unit would increase the banks Performance by 0.828 regardless of the banking system. Conclusion: The researcher recommended that the Kenyan banking sector should embrace Technology in order to tap in the untapped market through innovations for the customers to be able to conduct banking businesses at their own convenience.